Integracijski multikulturalizem ali multikulturnost integracije - Medica, Karmen (Monitor ISH, 2007)
Integration as a two-way adaptation of minorities and immigrant groups on the one hand, and the majority population on the other, is a response to the challenge of diverse cultures coexisting in the same society, including the groups' contributions to the community and their ongoing contacts with their original culture. This article contrasts different perceptions of multiculturalism, multiculturalism as a contemporary practice of integration and as a contemporary political alternative, and multiculturalism as monoand multidimensionality. Moreover, it compares multiculturalism with multicolourism in advertising and presents examples of integrational models, as well as the practices of Great Britain, Sweden and Slovenia.
Keywords: multikulturalizem; večkulturnost; priseljenci; manjšine; integracija